A Process View of Medical Practice by Modeling Communicative Acts - Maij, E.; van Reijswoud, V. E.; Toussaint, P. J.; Harms, E. H.; Zwetsloot-Schonk, J. H. M. (Methods of Information in Medicine, 2000)
The need of an electronic patient record with a process view on medical care is widely acknowledged. Characteristics of DEMO (Dynamic Essential Modeling of Organizations) suggest that with this methodology an adequate process view of medical practice can be obtained. In applying DEMO to the care process of the emergency department at the University Medical Centre Utrecht, it was investigated if DEMO fulfilled our expectations. This practical application showed that DEMO yields an adequate process view by a clear and comprehensible view of the core processes, responsibilities, co-ordination of activities, and a clear description of causal and conditional relations between activities.
Keywords: Business Process Modeling, Communicative Act, DEMO, EPR